EVALUATION OF PLANNING AND CONSUMPTION OF MEDICAL RESOURCES IN PRIMARY HEALTH CARE IN SERBIA - Jocić, Đorđe (HEALTH CARE, 2025)
Introduction/Aim: Efficient planning and consumption of medicines, medical and sanitary supplies, and laboratory reagents within the framework of Serbia's primary health care directly affect therapy availability, service quality, and the rational use of budgetary resources. Although a formal framework for centralized procurement exists, practice reveals significant discrepancies in criteria, procedures, and institutional approaches. The aim of this study was to examine how health care institutions plan their needs, what decision-making criteria they use, and the role of the Republic Health Insurance Fund (RHIF) in the evaluation and implementation of these plans.Methods: A quantitative study was conducted among 136 primary health care institutions and 26 RHIF branches, using a questionnaire designed in accordance with valid regulations and professional methodological guidelines. Data were analyzed in the Excel environment, using a binary matrix and thematic classification of responses.Results: Most institutions (84.6%) rely on historical consumption and RHIF guidelines, while only 8.8% use economic criteria. A multicriteria approach is used by just 5.1% of institutions. Internal evaluation is absent in 26.5% of cases, and information systems are mostly used for administrative purposes. A pattern of planning without analytical verification was observed, along with frequent shifting of responsibility to RHIF, which stated in its response that it did not perform evaluations nor apply analytical tools. Conclusion: Although the planning system formally meets regulatory requirements, it lacks an analytical foundation and functional evaluation. Establishing a standardized model based on clinical, economic, and epidemiological indicators, along with an active evaluative role of RHIF and two-way institutional feedback, represents a key step toward more rational and equitable management of health care resources.
Keywords: primary health care, needs planning, centralized procurement, medical resources, Republic Health Insurance Fund